1982
DOI: 10.1017/s0043174500041400
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chlorsulfuron or 2,4-D upon Diclofop-Methyl Efficacy in Oat (Avena sativa)

Abstract: Oat (Avena sativaL. ‘Elgin′) seedlings were treated with combinations of diclofop-methyl {methyl ester of 2-[4-(2,4-dichlorophenoxy)phenoxy] propanoic acid} and 2,4-D amine [dimethylamine salt of (2,4-dichlorophenoxy) acetic acid] or diclofop-methyl and chlorsulfuron {2-chloro-N-[[(4-methoxy-6-methyl-1, 3, 5-triazin-2-yl)amino] carbonyl] benzenesulfonamide} to determine the effect of the added herbicide on diclofop-methyl activity. Diclofop-methyl applied alone at rates of 0.50, 0.75, and 1.00 kg/ha killed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
1

Year Published

1986
1986
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 8 publications
0
15
0
1
Order By: Relevance
“…5A). Such an effect extended over 24 h tnay explain the action of auxin-like compounds, 2,4-D and dicamba, in partially overcoming the inhibitory effect of DM in the Avena straight growth test (Hall et al 1982, Shitnabukuro et al 1978. The 2,4-D analog, 2,6-D, which failed to stitnulate proton excretion (Fig.…”
Section: Coleoptile Growthmentioning
confidence: 98%
See 2 more Smart Citations
“…5A). Such an effect extended over 24 h tnay explain the action of auxin-like compounds, 2,4-D and dicamba, in partially overcoming the inhibitory effect of DM in the Avena straight growth test (Hall et al 1982, Shitnabukuro et al 1978. The 2,4-D analog, 2,6-D, which failed to stitnulate proton excretion (Fig.…”
Section: Coleoptile Growthmentioning
confidence: 98%
“…Therefore, simultaneous field application of DM and 2,4-D to control wild oat and broad-leaved weeds in wheat is not recommended due to the reduced phytotoxicity of DM (O'Sullivan et al 1977, Todd andStobbe 1974). The antagonism is reciprocal and has been demonstrated in tissue culture (Shimabukuro et al 1986), oat coleoptiles (Hall et al 1982, Shimabukuio et al 1978 and whole plants under greenhouse and field eonditions (Olson and Nalewaja 1981).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Thus chlorophenoxy herbicide antagonism of diclofopmethyl activity may be due to effects on H* efflux from cells. Chlorophenoxy herbicides can cause a substantial decrease in diclofop-methyl phytotoxicity (Hall et al, 1982a;Kafiz et al, 1989). If diclofop-methyl antagonism by chlorophenoxy herbicides is primarily due to their auxin-like effects on H* extrusion or other processes, then inhibition of auxin action must be an important factor in the mode of action of diclofop-methyl.…”
Section: Introductionmentioning
confidence: 99%
“…oats{Hall et al, 1982). Studies conducted at IO\va State University have shown that chlorsulfuron can be applied to Kentucky bluegrass at rates as high as 280 g/ha without any phytotoxic effects.…”
mentioning
confidence: 99%